Classical summation in commutative and noncommutative Lp-spaces - Defant, Andreas (Berkeley, Calif. Apress, 2011)
The aim of this research is to develop a systematic scheme that makes it possible to transform important parts of the by now classical theory of summation of general orthonormal series into a similar theory for series in noncommutative {dollar}L_p{dollar}-spaces constructed over a noncommutative measure space (a von Neumann algebra of operators acting on a Hilbert space together with a faithful normal state on this algebra).
1 Introduction -- 2 Commutative Theory -- 3 Noncommutative Theory.
Electronic reproduction.
Keywords: Commutative algebra; Noncommutative algebras; Functional analysis